Distribution and systematics of the freshwater genus Sirodotia (Batrachospermales, Rhodophyta) in North America - Necchi Júnior, Orlando [UNESP]; Sheath, Robert G.; Cole, Kathleen M. (Phycological Soc Amer Inc, 1993)
Multivariate morphometrics and image analysis were used to determine the number of well-delineated infrageneric taxa of Sirodotia in North America. Three groupings were distinguished from 25 populations examined from Newfoundland and Quebec in the north to central Mexico in the south. These groupings were statistically related to 10 type specimens, and the following species were recognized: Sirodotia huillensis (Welwitsch ex W. et G. S. West) Skuja (syn. S. ateleia Skuja), S. suecica Kylin (syn. S. acuminata Skuja ex Flint and S. fennica Skuja), and S. tenuissima (Collins) Skuja ex Flint. These species are differentiated on the basis of whorl shape and degree of separation at maturity (S. suecica, rounded and appressed; S. huillensis and S. tenuissima, truncated apex and separated), the density of spermatangia (S. huillensis, dense clusters, S. suecica and S. tenuissima, sparsely aggregated), and the mode of germination of the gonimoblast initial (S. suecica and S. tenuissima,from the nonprotuberant side of the fertilized carpogonium; S. huillensis from the protuberant side). Sirodotia huillensis was found only in the desert-chaparral, whereas S. suecica and S. tenuissima occurred from south-temperate to boreal regions in cool (temperature 8-18-degrees-C), low ion (specific conductance 10-99 muS.cm-1), and mildly acidic to neutral (pH 5.7-7.3) waters.
Keywords: Batrachospermales; Chaparral; Desert; Rhodophyta; North America; Sirodotia huillensis; Sirodotia suecica; Sirodotia tenuissima